2022
DOI: 10.3390/ma15093027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steel Fiber and Specimen Geometric Dimensions on the Mechanical Properties of Ultra-High-Performance Concrete

Abstract: Ultra-high-performance concrete (UHPC) is an advanced concrete with superior mechanical strength, ductility and durability properties. However, the influence of steel fiber on its constitutive laws and the specimen geometric dimension effect on its strength had not been paid enough attention. To investigate the effect of steel fibers on the properties of UHPC, specimens with different fiber volume contents and fiber types were tested. Meanwhile, the mechanical properties of UHPC at different ages from 3 days t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Figure 6 a summarizes the influence of the steel fiber content on the improvement index of the direct tensile strength. All the studies agree that the direct tensile strength increases with an increase in the steel fiber content (up to 5 vol.% [ 88 , 93 ]), even reaching 3.2 times that of a UHPC without fiber reinforcement [ 79 ]. The size of the dog-bone specimen affects the improvement of the direct tensile strength by the fiber content [ 45 , 75 , 80 , 93 ].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Figure 6 a summarizes the influence of the steel fiber content on the improvement index of the direct tensile strength. All the studies agree that the direct tensile strength increases with an increase in the steel fiber content (up to 5 vol.% [ 88 , 93 ]), even reaching 3.2 times that of a UHPC without fiber reinforcement [ 79 ]. The size of the dog-bone specimen affects the improvement of the direct tensile strength by the fiber content [ 45 , 75 , 80 , 93 ].…”
Section: Resultsmentioning
confidence: 72%
“…Some studies have found that hooked-end fibers with a fiber length of 13~30 mm do not significantly improve the direct tensile strength [ 64 , 79 ]. Park et al [ 52 ] also obtained similar findings when studying the effect of ultra-long hooked-end fibers on the direct tensile strength of UHPC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue et al [ 28 ] suggested that the seawater–sea-sand concrete can be utilized to conserve river sand and fresh water by using polyoxymethylene fibers for improved resistance to early age cracking and enhanced mechanical properties. Fang et al [ 29 ] studied the effects of steel fibers having various geometries and shapes on the mechanical performance of ultra-high-performance concrete (UHPC). It was found that hook-ended steel fibers resulted in better improvement in the tensile performance compared with straight steel fibers.…”
Section: Introductionmentioning
confidence: 99%
“…UHPC has nearly three times the strength of normal concrete and high constructability, and it has been applied in the structural joint, bridge deck, or even the entire pedestrian bridge [ 10 , 11 , 12 , 13 ]. However, since they are mixed from different material components, the physicochemical properties of UHPC are quite different from normal construction materials, and the common construction characteristics remain to be investigated, especially the early age shrinkage behavior [ 14 , 15 , 16 , 17 ]. Due to the high content of binder and low water-to-cement ratio, the autogenous shrinkage of UHPC is much higher than normal concrete, and with the potential shrinkage crack, the material strength can be reduced over time [ 18 ].…”
Section: Introductionmentioning
confidence: 99%